Nanostructured Free‐Form Objects via a Synergy of 3D Printing and Thermal Nanoimprinting. Issue 5 (3rd December 2018) - Wu, Jumiati; Lee, Wei Li; Low, Hong Yee
Abstract: High‐resolution surface patterning has garnered interests as a nonchemical‐based surface engineering approach for creating functional surfaces. Applications in consumer products, parts for transportation vehicles, optics, and biomedical technologies demand topographic patterning on 3D net shape objects. Through a hybrid approach, high‐resolution surface texture is incorporated onto 3D‐printed polymers via direct thermal nanoimprinting process. The synergy of geometry design freedom in 3D printing and the high spatial resolution in nanoimprinting is demonstrated to be a versatile fabrication of high‐fidelity surface pattern (from 2 µm to 200 nm resolution) on convex, concave semicylindrical, and hemispherical objects spanning a range of surface curvatures. The novel hybrid fabrication is further extended to achieve a high‐resolution curved mold insert for rapid prototyping via injection molding. The versatility of the fabrication strategies reported here not only provides a post‐3D printing process that enhances the surface properties of 3D‐printed objects but also opens a new pathway to enable future study on the effects of combining microscale and nanoscale surface texture with macroscopic curvature. Both have been known, individually, as an effective approach to tune surface functionalities. Abstract : A two‐step thermal nanoimprint lithography combined with 3D printing for fabrication of high‐resolution surface feature on a free‐form 3D mold insert is reported. A mold insert designed with various curvatures and surface feature as low as 200 nm can be further used to replicate fine features on free‐form 3D object via nanoinjection molding.